The ramnent of medieval Christian attitudes towards Prophet Muhammad (p.b.u.h): a critical evaluation of Margoliouth's pathological theory - Aliyu, Muhammad Akilu; Abdul Rahim, Adibah (Zes Rokman Resources, 2016)
The emergence and expansion of Islam have been considered a severe challenge to Christianity. With its significant expansion, the Christians became so much exasperated. Thus, they started searching for every possible avenue to do away with it. In medieval period, many intellectual and military attacks were lunched against Islam. One of the strategies was to create false theories which portrayed Prophet MuÍammad (p.b.u.h) negatively and damagingly. The most absurd theory was ‘pathological theory’ which attempted to charge the Prophet (p.b.u.h) of being epileptic. Although many attempts have been made by both Muslims and some less biased Christian scholars to fish this theory out from the scene, it continues to have relevance even in some of the well-learned contemporary Christian scholar’s writings. This study attempts to analyse and evaluate David Samuel Margoliouth’s views on this theory since he is one of the well-versed and contemporary Islamists. In doing so, analytical, comparative and evaluative methods would be used.